KONSEP SEMIOTIK CHARLES JENCKS DALAM ARSITEKTUR POST-MODERN - Dwi Murdiati (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractThe aims of this work are to know and to explain Charles Jencks’ semiotic concept of postmodern architecture. In one hand, Jencks’ postmodern architecture is criticism on modern and modern-late architecture. Jencks stresses on both differences that modern and modern-late architecture are based on a single coding only and postmodern architecture is based on double coding in their style. In other one, Jencks’ postmodern architecture is a semiotic entity that has to seen as a sign.This research is the figure factual history research. It wasbased on primary and secondary literature. It used description,interpretation and heuristic method.Jencks’s semiotic conception of postmodern architecture hasadopted dualism semiotic of Saussuran like signifier-signified,langue-parole, denotation-connotation, and paradigmatic-sintagmatic. It also has adopted trilateral semiotic of Piercean like index, icon, symbol and sintagmatic, syntactic, semantic.Keywords: Postmodern architecture, double coding, dualismsemiotic, trial semioti.